Analyzing the impact of the shift to remote work mode on middle managers' well-being in the pandemic - Juan Sandoval-Reyes; Lorenzo Revuelto-Taboada; Edison Jair Duque-Oliva (European Research on Management and Business Economics (ERMBE), 2023)
The shift to remote work mode significantly impacts the way people work, especially middle managers, who play a fundamental role in organizations. There is a broad consensus that they have a key responsibility in deploying strategies, and in terms of operations and organizational culture. Based on the responses of 200 managers from five Latin American countries working in several economic sectors, the effects of remote work demands on their levels of perceived work stress and general well-being were examined in this study. Through partial least squares structural equation modeling, the positive effect of remote work demands on work stress was verified. The analysis also suggested a competitive mediating effect of role transitions on the relationship between work stress and well-being. The study also provides theoretical and practical implications for human resource management and a design of flexible labor policies from a sustainability perspective.
Keywords: M12; M15; M54; I10; I31; 650; Middle managers; Remote work mode; Teleworking; Well-being